Infant Health and Development Program (IHDP): Enhancing the Outcomes of Low Birth Weight, Premature Infants in the United States, 1985-1988 - Gross, Ruth T. ([Verlag nicht ermittelbar], 1993)
The Infant Health and Development Program was a collaborative, randomized, longitudinal, multisite clinical trial designed to evaluate the efficacy of comprehensive early intervention in reducing the developmental and health problems of low birth weight, premature infants. An intensive intervention extending from hospital discharge to 36 months corrected age was administered between 1985 and 1988 at eight different sites. The study sample of infants was stratified by birth weight (2,000 grams or less, 2,001-2,500 grams) and randomized to the Intervention Group or the Follow-Up Group. The Intervention Group received home visits, attendance at a special child development center, and pediatric follow-up. The Follow-Up Group received only the pediatric follow-up component of the program. Measures of cognitive development, behavioral status, health status, and other variables were collected from both groups at predetermined time points. Cognitive development was assessed by the Stanford-Binet Intelligence Scale, the Bayley Mental and Motor Scales, the Peabody Picture Vocabulary Test--Revised, and the Beery-Buktenica Developmental Test of Visual Motor Integration. Behavior problems were measured using the Richman-Graham Behavior Checklist and Achenbach's Child Behavior Checklist. Health status was evaluated through the dimensions of morbidity (defined as the presence or absence of health conditions), functional status (defined by limitations in activities of daily living due to health problems), changes in physical growth, and maternal perception of the child's health. The many other variables and indices in the data collection include site, pregnancy complications, child's birth weight and gestation age, birth order, child's gender, household composition, day care arrangements, source of health care, quality of the home environment, parents' race and ethnicity, and maternal age, education, IQ, and employment.